2022
DOI: 10.3390/pharmacy10060147
|View full text |Cite
|
Sign up to set email alerts
|

Generating Practice-Based Evidence in the Use of Guideline-Recommended Combination Therapy for Secondary Prevention of Acute Myocardial Infarction

Abstract: Background: Clinical guidelines recommend beta-blockers, angiotensin-converting enzyme inhibitors/angiotensin-receptor blockers, and statins for the secondary prevention of acute myocardial infarction (AMI). It is not clear whether variation in real-world practice reflects poor quality-of-care or a balance of outcome tradeoffs across patients. Methods: The study cohort included Medicare fee-for-service beneficiaries hospitalized 2007–2008 for AMI. Treatment within 30-days post-discharge was grouped into one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 128 publications
0
1
0
Order By: Relevance
“…Using comprehensive medication management and provider education, pharmacists were able to optimize treatment for these patients and achieve optimal clinical outcomes. On the other hand, Schroeder et al, in their observational study of patients with acute myocardial infarction, examined whether deviation from the guidelines is always a bad case [ 13 ]. Their study findings refuted this claim and reported that there was a trade-off between the beneficial and detrimental effects of the guideline-based treatment in their study sample.…”
mentioning
confidence: 99%
“…Using comprehensive medication management and provider education, pharmacists were able to optimize treatment for these patients and achieve optimal clinical outcomes. On the other hand, Schroeder et al, in their observational study of patients with acute myocardial infarction, examined whether deviation from the guidelines is always a bad case [ 13 ]. Their study findings refuted this claim and reported that there was a trade-off between the beneficial and detrimental effects of the guideline-based treatment in their study sample.…”
mentioning
confidence: 99%